Synthesis method of Fe and N co-doped nanotube-coated microspheres and application of Fe and N co-doped nanotube-coated microspheres in catalytic degradation of organic pollutants
By using Fe and N co-doped nanotube-wrapped microsphere materials as catalysts to activate the persulfate-based in-situ chemical oxidation (ISCO) agent, the problem of low sulfamethoxazole removal efficiency in the existing technology was solved and achieved Efficient degradation effect.
Patent Information
- Application Number
- CN202411483688.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art has poor removal effect on sulfamethoxazole, and its hydrophilicity makes it unsuitable for activation and adsorption, resulting in low removal efficiency.
Using birdoside as the C and N front -wheel drive, mixed with the iron source under acidic conditions to perform hydrophilic reactions, and then thermal solution obtained the FE and N co -doped nano -tube wrapped in micron ball materials as a catalyst. Pass chemical oxidation (ISCO) agent, improves the degradation efficiency of sulfonamolizol.
This catalyst has a wealth of medium and micro -pores. The high -ratio surface area, which forms a 3D structure to increase the contact area with the reactant, promote the uniform distribution of active substances, and significantly improve the degradation efficiency of sulfa metharomodolzol.
Smart Images

Figure BDA0005098164700000101 
Figure BDA0005098164700000102 
Figure BDA0005098164700000111
Abstract
Description
Technical Field
[0001] The invention belongs to the field of environment, and particularly relates to a Fe and N co-doped nanotube-wrapped micron ball material for efficiently degrading sulfamethoxazole. Background Art
[0002] Sulfamethoxazole is a typical sulfonamide antibiotic and one of the most widely used antibiotics. It has been widely used in animal husbandry, aquaculture and the prevention and treatment of diseases caused by microorganisms. However, it is worth noting that only 10% to 50% of sulfamethoxazole can be effectively metabolized in organisms, and the rest is excreted from the human body and enters the natural environment. Therefore, the presence of sulfamethoxazole has been detected in sediments, sewage sludge, soil and wastewater in many countries and regions. Especially in water media, its concentration ranges from hundreds to thousands of nanograms per liter.
[0003] Due to the poor microbial degradability of sulfamethoxazole, the existing biological treatment processes are not effective enough for the removal of sulfamethoxazole, resulting in a low removal efficiency of sulfamethoxazole. In addition, its hydrophilicity makes it unsuitable for activation and adsorption. Therefore, persulfate-based in situ chemical oxidation (ISCO) has been used to eliminate sulfamethoxazole due to the generation of strong reactive oxygen species (ROS). The participating sulfate radicals (SO4·) are generated by the activation of persulfates (referring to peroxymonosulfate (PMS) and peroxydisulfate (PMS), have a wide pH range, can work in acidic and alkaline media, and have a higher oxidation potential (2.5-3.1.V) compared to hydroxyl (OH·) radicals (1.9-2.7V).
[0004] Nanocarbon materials have shown great potential as catalysts for promoting PMS activity. This potential is mainly attributed to their rich surface functional groups, defects and tunable work functions. Researchers have found that defect structures and oxygen-containing functional groups in carbon materials can promote PMS activation and enhance the removal of difficult-to-degrade pollutants. In addition, in sp 2-The introduction of heteroatoms (especially nitrogen atoms) into the hybrid carbon framework helps to improve the catalytic performance. This enhancement stems from their ability to create various active sites, generate new defects, impart strong chemical stability and improve conductivity. Despite this, the catalytic ability of carbon materials themselves is limited, and the catalytic activity can be enhanced by adding transition metals (such as Fe, Co and Ni) to various carbon-based substrates. In the existing carbon-supported iron catalysts that are activated to promote the activity of PMS, most of them use organic framework structures as carriers to promote the dispersibility of active components. The carrier process of the organic framework structure is complicated, the cost of the organic framework structure is high, the loss is high during the pyrolysis process, the yield is low, and the metal organic framework precursor also involves other metal components and iron metals for coordination, and this method cannot regulate the morphology of the catalyst. The obtained related carbon-based materials have a small specific surface area, are easily decomposed at high temperature, and have a low yield. As for the preparation of guanosine as a carbon and nitrogen precursor to promote the activity of PMS, there is no relevant literature research. Summary of the invention
[0005] In order to solve the problems in the background technology, the present invention provides a Fe and N co-doped catalyst which uses guanosine as a C and N precursor, mixes with an iron source under acidic conditions, performs a hydrothermal reaction, and then further pyrolyzes to obtain a spherical structure of carbon tubes. The catalyst uses biological molecules guanosine and ferric nitrate nonahydrate as raw materials, has low preparation cost and simple method, and does not require the use of additional template agents; the pore size is rich, which is conducive to electron transfer and exposure of active sites; the nanotubes are wound around the surface of the microspheres to form a 3D structure, which further increases the contact area with the reactants and is more conducive to adsorption and mass transfer; at the same time, the wound nanotubes promote the uniform distribution of active substances, reduce metal agglomeration, and are conducive to the catalytic reaction.
[0006] In order to achieve the above technical effects, the technical solution adopted by the present invention is:
[0007] The synthesis method of Fe and N co-doped nanotube-wrapped microsphere material is as follows:
[0008] (1) adding guanosine to deionized water and adding sulfuric acid, stirring and mixing under heating conditions to obtain a light yellow solution, and adding ferric nitrate to the light yellow solution to obtain a brown solution;
[0009] (2) Transfer the brown solution obtained in step (1) to a polytetrafluoroethylene-lined reactor, cover the reactor with a lid, and place the reactor in a dry air-blast oven for heating and reaction at 160°C to 190°C for 9 to 24 hours;
[0010] (3) After the reaction is completed, wait for the reactor to cool to room temperature, use a Buchner funnel to filter out the solid, and use deionized water to wash until the washing liquid is clear. Place the washed solid in a 60°C oven and dry it for 12 hours;
[0011] (4) Grinding the dried solid, taking the ground solid and placing it in a porcelain crucible, heating it to 900-1000°C for pyrolysis at a heating rate of 5-10°C / min in a N2 atmosphere, cooling it to room temperature after pyrolysis, and taking out the solid;
[0012] (5) The solid obtained in step (4) is washed with 0.1% dilute hydrochloric acid, and then washed with deionized water to neutralize the solid. After drying, Fe and N co-doped nanotube-wrapped microsphere material is obtained.
[0013] Furthermore, in step (1), the concentration of guanosine in water is less than 0.1 g / mL, and the mass ratio of guanosine to ferric nitrate is 3:1 to 3; more preferably: 3:1.8 to 3:2.2.
[0014] Furthermore, the molar concentration of sulfuric acid in step (1) is 0.1-0.5 M; the heating conditions are 60-90° C., and the heating time is 8-15 min.
[0015] Furthermore, preferably, the heating reaction in step (2) is carried out at 180° C. for 12 hours.
[0016] Furthermore, preferably, the pyrolysis temperature in step (4) is 900° C. and the pyrolysis time is 1 to 4 hours.
[0017] The synthesized Fe and N co-doped nanotube-wrapped microsphere material is used as a catalyst to activate PMS to degrade one or more organic pollutants in sulfamethoxazole, tetracycline, enrofloxacin and ofloxacin.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] The Fe and N co-doped nanotube-wrapped microsphere material synthesized by the present invention is spherical in shape, and the surface of the sphere is wrapped with entangled carbon nanotubes. The catalyst of this morphology has abundant mesopores and micropores and a very high specific surface area. The present invention further studies the use of the catalyst as a catalyst for activating PMS to degrade organic pollutants such as sulfamethoxazole, tetracycline, enrofloxacin, and ofloxacin, and has excellent degradation activity, providing important guiding significance for its application in the field of catalysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The XRD spectrum of the carbon tube-wrapped spherical structure catalyst Fe-Guo-900 prepared in Example 1;
[0021] Figure 2 It is a N2 adsorption-desorption curve diagram of the carbon tube-wrapped spherical structure catalyst Fe-Guo-900 prepared in Example 1;
[0022] Figure 3The transmission electron microscope image of the carbon tube-wrapped spherical structure catalyst Fe-Guo-900 prepared in Example 1;
[0023] Figure 4 This is the HADDF-STEM transmission electron microscopy image of the carbon tube-wrapped spherical structure catalyst Fe-Guo-900 prepared in Example 1.
[0024] Figure 5 This is a transmission electron microscope image of Fe-Guo-900 prepared in Example 1;
[0025] Figure 6 This is the HADDF-STEM transmission electron microscopy image of Fe-Guo-900 prepared in Example 1;
[0026] Figure 7 EDS-mapping images of N, C, Fe and O of Fe-Guo-900 prepared in Example 1;
[0027] Figure 8 is the XRD spectrum of Fe-Guo-1;
[0028] Fig. 9 is the N2 adsorption-desorption curve of Fe-Guo-1;
[0029] Fig.10 is the pore size distribution diagram of Fe-Guo-1;
[0030] Fig.11 This is the scanning electron microscope image of Fe-Guo-1;
[0031] Fig.12 It is the transmission electron microscope image of Fe-Guo-1;
[0032] Fig.13 HADDF-STEM image of Fe-Guo-1;
[0033] Fig.14 EDS-mapping images of N, C, Fe, and O of Fe-Guo-1;
[0034] Fig.15 is the XRD spectrum of Fe-Guo-3;
[0035] Fig.16 is the N2 adsorption-desorption curve of Fe-Guo-3;
[0036] Fig.17 is the pore size distribution diagram of Fe-Guo-3;
[0037] Fig.18 This is the scanning electron microscope image of Fe-Guo-3;
[0038] Fig.19 It is the transmission electron microscope image of Fe-Guo-3;
[0039] Fig. 20 HADDF-STEM image of Fe-Guo-3;
[0040] Fig.21 EDS-mapping images of N, C, Fe, and O of Fe-Guo-3;
[0041] Fig. 22 is the XRD spectrum of Fe-Guo-700;
[0042] Fig.23 This is the scanning electron microscope image of Fe-Guo-700;
[0043] Fig.24 is the XRD spectrum of Fe-Guo-800;
[0044] Fig.25 This is the scanning electron microscope image of Fe-Guo-800;
[0045] Fig.26 This is a scanning electron microscope image of Guo-900;
[0046] Fig. 27 This is a scanning electron microscope image of Guo-block. DETAILED DESCRIPTION
[0047] The present invention is described in detail below with reference to the embodiments.
[0048] Example 1
[0049] 1. Add 3.0 g of guanosine to 35 mL of deionized water, add 570 μL of sulfuric acid, and heat at 80 °C at 400 rpm for 10 min to obtain a light yellow solution. Then add 2.0 g of Fe(NO3)3·9H2O to the solution to obtain a brown solution.
[0050] 2. Transfer the obtained brown solution to a 100 mL polytetrafluoroethylene liner reactor, cover the reactor with a lid, and place the reactor in a dry forced air oven for hydrothermal reaction at 180°C for 12 hours.
[0051] 3. After the reaction is completed, wait for the reactor to cool to room temperature. Use a Buchner funnel to filter out the solid, and wash it with deionized water until the washing liquid is clear. Put the washed solid into a 60°C oven and dry it for 12 hours.
[0052] 4. Use a mortar to grind the solid obtained after drying evenly. Take 1.0g of the ground solid and put it into a porcelain crucible. In a N2 atmosphere, heat it to 900℃ at a heating rate of 5℃ / min and keep it warm for 2h. Wait for the tube furnace to cool to room temperature and take out the solid.
[0053] 5. Wash the obtained solid powder with 0.1% mass fraction of dilute hydrochloric acid for 12 hours, then wash it with deionized water to neutralize it and remove impurities attached to the surface. Take out the washed powder and put it into a 60°C oven to dry for 12 hours to obtain Fe and N co-doped nanotube-wrapped microsphere catalyst (Fe-Guo-900).
[0054] Figure 1 This is the XRD spectrum of Fe-Guo-900; peaks of amorphous carbon and Fe2O3 can be observed in the spectrum.
[0055] Figure 2 It is the N2 adsorption-desorption curve of Fe-Guo-900; Figure 3 is the pore size distribution diagram of Fe-Guo-900; Figure 2 It can be seen that the Fe and N co-doped nanotube-wrapped microsphere catalyst has abundant mesopores and micropores, with a specific surface area of 402.32 m 2 / g, pore volume is 0.41m 2 / g, of which micropores are 0.11m 2 / g, and the mesopore volume is 0.22m 2 / g.
[0056] Figure 4 This is a scanning electron microscope image of Fe-Guo-900. It can be observed that the catalyst is spherical as a whole, and the surface of the sphere is wrapped with entangled carbon nanotubes.
[0057] Figure 5 This is the transmission electron microscope image of Fe-Guo-900, from which it can be observed that the catalyst is a solid sphere as a whole.
[0058] Figure 6 This is the HADDF-STEM transmission electron microscope image of Fe-Guo-900. Hollow circles can be observed on the solid sphere, which are the tube openings of carbon nanotubes.
[0059] Figure 7 This is the EDS-Mapping image of Fe-Guo-900. It can be observed that C, N, and O are evenly distributed, while Fe is distributed in clusters. Combined with the HADDF-STEM transmission electron microscopy image, it can be found that their positions overlap, indicating that the Fe element is inside the carbon tube.
[0060] Example 2
[0061] Compared with Example 1, Example 2 differs in that the pyrolysis temperature in step 4 is changed to 1000° C., and other operations are the same as Example 1.
[0062] When the pyrolysis temperature is 1000 °C, a spherical structure wrapped by carbon tubes can also be obtained.
[0063] Example 3
[0064] Compared with Example 1, Example 3 differs in that the pyrolysis holding time in step 4 can also be changed to 1 hour, and other operations are the same as Example 1.
[0065] Example 4
[0066] Compared with Example 1, Example 4 differs in that the pyrolysis holding time in step 4 can also be changed to 3 hours, and the other operations are the same as Example 1.
[0067] Embodiment a
[0068] Example a Compared with Example 1, the iron nitrate nonahydrate in Example 1 was replaced with 1 g. A solid spherical structure (Fe-Guo-1) without nanotubes on the surface was obtained.
[0069] Figure 8 This is the XRD spectrum of Fe-Guo-1, in which the peaks of amorphous carbon and Fe2O3 can be observed;
[0070] Fig. 9 is the N2 adsorption-desorption curve of Fe-Guo-1, Fig.10 is the pore size distribution diagram of Fe-Guo-1; Fig.10 It can be seen that the specific surface area of Fe-Guo-1 is 321.11m 2 / g, pore volume is 0.34m 2 / g, of which micropores are 0.090m 2 / g, and the mesopore volume is 0.23m 2 / g.
[0071] Fig.11 The scanning electron microscope image of Fe-Guo-1 shows that Fe-Guo-1 is a spherical structure, but there is no carbon tube wrapped on the surface. Guanine decomposed from iron nitrate and guanosine during the hydrothermal process is an important component for constructing the carbon tube morphology. If the dosage is reduced, iron nitrate and guanosine react completely to form carbon microspheres during the hydrothermal process, and there is no excess free iron ions to react with the remaining guanine decomposed from guanosine, and the special morphology wrapped by nanotubes cannot be formed.
[0072] Fig.12 This is the transmission electron microscope image of Fe-Guo-1, which shows that Fe-Guo-1 is a solid spherical structure.
[0073] Fig.13 This is the HADDF-STEM transmission electron microscopy image of Fe-Guo-1. It can be observed that there is particle distribution, but it is not the hollow circle in Fe-Guo-900, indicating that its morphology is different.
[0074] Fig.14 This is the EDS Mapping image of Fe-Guo-1. It can be observed that Fe, C, N, and O are uniformly distributed. Fig.13 Combined, it shows that Fe-Guo-1 is Fe2O3 distributed in the form of particles.
[0075] Embodiment b
[0076] Example b Compared with Example 1, the iron nitrate nonahydrate in Example 1 was replaced with 3 g to obtain a solid spherical structure (Fe-Guo-3) without nanotubes wrapping on the surface.
[0077] Fig.15 This is the XRD spectrum of Fe-Guo-3. In addition to the peaks of amorphous carbon and Fe2O3, the peak of iron also appears. This is because with the increase in the amount of iron source, excess Fe is included in the formation process of carbon microspheres, causing iron to be generated at high temperature.
[0078] Fig.16 is the N2 adsorption-desorption curve of Fe-Guo-3, Fig.17 is the pore size distribution diagram of Fe-Guo-3;
[0079] Fig.18 The scanning electron microscope image of Fe-Guo-3 shows that Fe-Guo-3 is a spherical structure with no nanotubes entangled on the surface. During the hydrothermal process, the excess iron nitrate contacts guanosine before it is polymerized, and during the decomposition and polymerization of guanosine, the iron nitrate is coated, so that it cannot fully react with the polymer obtained by hydrothermal treatment of guanosine. These coated Fe generate iron elements at high temperatures and cannot be removed from the carbon microspheres, resulting in a waste of Fe sources. In addition, due to the excess of Fe, the guanine decomposed during the hydrothermal treatment of guanosine is not sufficient, so that the remaining Fe without excess guanine reacts into carbon nanotubes, so there is no nanotube entanglement.
[0080] Fig.19 This is the TEM image of Fe-Guo-3, which shows that Fe-Guo-3 is a solid spherical structure.
[0081] Fig. 20 This is the HADDF-STEM transmission electron microscopy image of Fe-Guo-3. It can be observed that a small part of the particles are accumulated, indicating that the Fe in Fe-Guo-3 is not evenly distributed.
[0082] Fig.21 This is the EDS Mapping image of Fe-Guo-3. It can be observed that C, N, and O are evenly distributed. Fig. 20 Combined, it shows that Fe-Guo-3 is an uneven distribution of Fe.
[0083] Example c
[0084] The difference between Example c and Example 1 is that the pyrolysis temperature in step 4 is changed to 700°C, and the other operations are the same as Example 1. A spherical structure (Fe-Guo-700) without carbon tubes wrapped around the surface is obtained, which is because the temperature is not enough and the tubular structure is not formed.
[0085] Fig. 22 This is the XRD spectrum of Fe-Guo-700, in which amorphous carbon can be observed.
[0086] Fig.23 This is a scanning electron microscope image of Fe-Guo-700. It can be observed from the spectrum that Fe-Guo-700 is a spherical structure with no carbon tubes wrapped around the surface.
[0087] Embodiment d
[0088] The difference between Example d and Example 1 is that the pyrolysis temperature in step 4 is changed to 800°C, and the other operations are the same as Example 1. A spherical structure (Fe-Guo-800) without carbon tubes wrapped around the surface is obtained, which is because the temperature is not enough and the tubular structure is not formed.
[0089] Fig.24 This is the XRD spectrum of Fe-Guo-800, in which amorphous carbon can be observed.
[0090] Fig.25 This is a scanning electron microscope image of Fe-Guo-800. It can be observed from the spectrum that Fe-Guo-800 is a spherical structure with no carbon tubes wrapped around the surface.
[0091] Comparative Example 1
[0092] Comparative Example 1 is different from Example 1 in that no ferric nitrate nonahydrate is added, and other operations are the same as Example 1. A carbon microsphere structure (Guo-900) with a rough surface is obtained, because guanosine can be decomposed into guanine and ribose, and ribose and guanine form a carbon-nitrogen polymer and form a sphere during the hydrothermal process. However, due to the absence of ferric nitrate nonahydrate, no tubular structure is formed.
[0093] Fig.26 This is a scanning electron microscope image of Guo-900.
[0094] Comparative Example 2
[0095] Comparative Example 2 is different from Example 1 in that sulfuric acid is not added, and other operations are the same as Example 1, and an irregular block structure (Guo-block) is obtained. This is because without adding sulfuric acid, 3g of guanosine cannot be completely dissolved and decomposed at 80°C, resulting in uneven morphology through hydrothermal reaction and thermal decomposition.
[0096] Fig. 27 This is a scanning electron microscope image of Guo-block.
[0097] Application Example 1
[0098] Prepare 100 mL of 10 mg / L sulfamethoxazole aqueous solution, add 15 mg of the catalyst of the embodiment to the sulfamethoxazole aqueous solution, and adsorb and balance on a magnetic stirrer at 25° C. and a stirring rate of 400 rpm for half an hour. Then add 0.5 mmol / L PMS to start the degradation reaction, take samples at 5 min, 10 min, 15 min, 20 min, 25 min, and 30 min of the reaction, filter out the catalyst with a 0.22 μm filter, and use high performance liquid chromatography to determine the concentration of sulfamethoxazole in the solution.
[0099] After only 5 minutes of reaction, the removal rate of sulfamethoxazole can reach 73.2%, after 10 minutes of reaction, the removal rate of sulfamethoxazole can reach 84.8%, after 15 minutes of reaction, the removal rate of sulfamethoxazole can reach 90.5%, after 20 minutes of reaction, the removal rate of sulfamethoxazole can reach 93.7%. After 25 minutes of reaction, the removal rate of sulfamethoxazole can reach 95.5%, after 30 minutes of reaction, the removal rate of sulfamethoxazole can reach 96.1%, and after 40 minutes of reaction, the removal rate of sulfamethoxazole can reach 97.5%. The results are shown in Table 1 below.
[0100] Table 1
[0101]
[0102] The samples of Example a and Example b were used and measured according to the method of Application Example 1. The results are shown in Table 2 below:
[0103] Table 2
[0104]
[0105] After each reaction, Fe-Guo-3 and Fe-Guo-900 of Example 1 were recovered and washed several times with deionized water, dried in an oven at 60°C and reused. After the fifth cycle, the degradation rate of Fe-Guo-3 dropped to 76.1%, and the degradation rate of Fe-Guo-900 dropped to 86.8%. This is because the active sites of Fe-Guo-3 are on the surface of the microspheres and the metal is partially agglomerated. After several reactions, the active sites are lost.
[0106] Using the samples of Example c and Example d with pyrolysis temperatures of 700°C and 800°C, the results are shown in Table 3 below according to the method of Application Example 1:
[0107] Table 3
[0108]
[0109] Application Example 2
[0110] Based on the application of the catalyst prepared in Example 1, Application Example 2 is different from Application Example 1 in that after preparing a 10 mg / L sulfamethoxazole solution, the pH of the sulfamethoxazole solution is adjusted to 3, 5, 7, 9 and 11 using 1 mol / L dilute hydrochloric acid and 5 mol / L sodium hydroxide. The results are shown in Table 4 below.
[0111] Table 4
[0112]
[0113] Application Example 3
[0114] Based on the catalyst prepared in Example 1, different from Application Example 1, when the degradation reaction temperature of sulfamethoxazole is 20° C. and 30° C., the results are shown in Table 5 below:
[0115] Table 5
[0116]
[0117] Application Example 4
[0118] Based on the catalyst prepared in Example 1, the difference from Application Example 1 is that the amount of catalyst added is 10 mg and 20 mg. The results are shown in Table 6 below:
[0119] Table 6
[0120]
[0121] Application Example 5:
[0122] Based on the catalyst prepared in Example 1, the difference from Application Example 1 is that the amount of PMS added is 0.25 mmol / L and 1.0 mmol / L. The results are shown in Table 7 below:
[0123] Table 7
[0124]
[0125] Application Example 6:
[0126] Based on the catalyst prepared in Example 1, different from Application Example 1, chloride ion anti-interference factor was added, and the degradation of sulfamethoxazole was measured in the presence of different concentrations of chloride ions. The results are shown in Table 8 below:
[0127] Table 8
[0128]
[0129] Application Example 7:
[0130] Based on the catalyst prepared in Example 1, different from Application Example 1, hydrogen phosphate anti-interference factor was added, and the degradation of sulfamethoxazole was measured in the presence of different concentrations of hydrogen phosphate. The results are shown in Table 9 below:
[0131] Table 9
[0132]
[0133]
[0134] Application Example 8:
[0135] Based on the catalyst prepared in Example 1, different from Application Example 1, bicarbonate anti-interference factor was added, and the degradation of sulfamethoxazole was measured in the presence of different concentrations of bicarbonate. The results are shown in Table 10 below:
[0136] Table 10
[0137]
[0138] Application Example 9:
[0139] Based on the catalyst prepared in Example 1, different from Application Example 1, humic acid (HA) interference factor was added, and the degradation of sulfamethoxazole was measured in the presence of different concentrations of humic acid. The results are shown in Table 11 below:
[0140] Table 11
[0141]
[0142]
[0143] Application Example 10:
[0144] Based on the catalyst prepared in Example 1, the difference from Application Example 1 is that the pollutants are different. The degradation of 10 mg / L tetracycline was measured. The results are shown in Table 12 below:
[0145] Table 12
[0146]
[0147] Application Example 11:
[0148] Based on the catalyst prepared in Example 1, the difference from Application Example 1 is that the pollutants are different. The degradation of 10 mg / L enrofloxacin was measured. The results are shown in Table 13 below:
[0149] Table 13
[0150]
[0151] Application Example 12:
[0152] Based on the catalyst prepared in Example 1, the difference from Application Example 1 is that the pollutants are different. The degradation of 10 mg / L ofloxacin was measured. The results are shown in Table 14 below:
[0153] Table 14
[0154]
Claims
1. A method for synthesizing Fe and N co-doped nanotube-wrapped microsphere material, characterized in that: The synthesis method of Fe and N co-doped nanotube-wrapped microsphere material is as follows: (1) adding guanosine to deionized water and adding sulfuric acid, stirring and mixing under heating conditions to obtain a light yellow solution, and adding ferric nitrate to the light yellow solution to obtain a brown solution; the mass ratio of guanosine to ferric nitrate is 3:1-3; (2) transferring the brown solution obtained in step (1) to a polytetrafluoroethylene-lined reactor for heating reaction at 160° C. to 190° C. for 9 to 24 hours; (3) After the reaction is completed, the reactants are cooled to room temperature, filtered to obtain a solid, washed, and dried; the dried solid is ground, and the ground solid is placed in a porcelain crucible, heated to 900-1000°C in a N2 atmosphere at a heating rate of 5-10°C / min for pyrolysis, cooled to room temperature after pyrolysis, and the solid is taken out, washed, and dried to obtain a Fe and N co-doped nanotube-wrapped microsphere material; specifically, a nanotube structure wrapped around the surface of the microsphere.
2. The method for synthesizing the Fe and N co-doped nanotube-wrapped microsphere material according to claim 1, characterized in that: The concentration of guanosine in step (1) water is less than 0.1 g / mL.
3. The method for synthesizing the Fe and N co-doped nanotube-wrapped microsphere material according to claim 1, characterized in that: Step (1) The molar concentration of sulfuric acid in deionized water is 0.1-0.5M; the heating condition is 60-90°C, and the heating time is 8-15min.
4. The method for synthesizing the Fe and N co-doped nanotube-wrapped microsphere material according to claim 1, characterized in that: The mass ratio of guanosine to ferric nitrate in step (1) is 3:1.8-2.
2.
5. The method for synthesizing the Fe and N co-doped nanotube-wrapped microsphere material according to claim 1, characterized in that: The heating reaction in step (2) is carried out at 180° C. for 12 hours.
6. The method for synthesizing the Fe and N co-doped nanotube-wrapped microsphere material according to claim 1, characterized in that: The pyrolysis time of step (3) is 1 to 4 hours.
7. The Fe and N co-doped nanotube-wrapped microsphere material synthesized according to the method of any one of claims 1 to 6, characterized in that: The nanotube structure is wrapped around the surface of the microsphere to form a 3D structure.
8. Use of the Fe and N co-doped nanotube-wrapped microsphere material synthesized according to the method of any one of claims 1 to 6 as a catalyst for degrading organic pollutants.
9. The use according to claim 8, characterized in that: The catalyst is used to activate PMS to degrade one or more organic pollutants in sulfamethoxazole, tetracycline, enrofloxacin and ofloxacin.
Citation Information
Cited By
Multivalent bimetallic oxide ceramic catalyst as well as preparation method and application thereof
CN121648937A